Pembangunan Pariwisata Berkelanjutan Pada Objek Wisata Desa Studi Kasus: Objek Wisata Embung Telaga Dapur Umum Desa Sukaraja Kecamatan Logas Tanah Darat Kabupaten Kuantan Singingi - Ruspianda, Riki; Yuliana, Dhina; Pratiwi, Retni; Karina, Rana (Universitas Riau, 2025)
This research is Entitled Sustainable Tourism Development In Village Tourism Objects: A Case Study of Embung Telaga Dapur Umum Tourism Object in Sukaraja Village, Logas Tanah Darat District, Kuantan Singingi Regency.